Education of foreign children - integration or disintegration of identity - Orłowska, Beata A. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper points to new difficulties and new expectations towards the Polish school. The presence of a greater number of immigrant students results in the school and teachers having to face new challenges. However, one often forgets that pupils too are put in a new school and in a new cultural situation.
Keywords: identity; migration; school; education; foreign students